Komunikasi Interpersonal Mahasiwa dengan Menggunakan Bahasa Jawa sebagai Identitas Etnis Jawa - Nadine Sekar Mustikaningari; Puri Kusuma Dewi Putri (Journal on Education, 2024)
Students have an important role in preserving the Javanese language as a symbol and identity for Javanese people by using it as a language of communication in everyday life and on campus. The aim of this research is to analyze the existence of the use of Javanese in interpersonal communication among students using symbolic theory. This research uses a descriptive qualitative approach. Data collection used interviews with students in Semarang City and experts in Javanese Language and Culture. The results of the research show that the use of Javanese in interpersonal communication among students in Semarang City has a low existence because it is no longer the main language and for formal interpersonal communication in the campus environment, the national language, namely Indonesian, is more commonly used. Therefore, students must study Javanese, continue to use Javanese well and correctly intensively as a language of daily instruction and to communicate with other people formally and informally.